Power system transient analysis using scale selection wavelet transform - Tan R.H.G.; Ramachandaramurthy V.K. (2023)
Power system transient analysis using scale selection wavelet transform is presented in this paper. The scale selection approach selectively performs continuous wavelet transform from scale 1 to scale 70, thus covering the typical power system transient frequency range. This creates a wavelet time scale known as Transient Zone between scale 1 to scale 70. For wavelet scale analysis, the scale is used to estimate the transient frequency, scale and energy. For time analysis, the wavelet scales that correspond to the highest energy in the wavelet scale analysis is selected to create the segmentation window to extract the entire transient disturbances. Wavelet scale 4 is selected to locate the actual time where the transient initially takes place to determine its magnitude, duration and over voltage. The experimental results show excellent performance in terms of effectively detecting, localizing, segmenting and estimating the energy, frequency, magnitude, duration and over voltage of the transient disturbance, thus enabling the differentiation between oscillatory and impulsive transients. 2009 IEEE.